RELATIONSHIP FAMILY SUPPORT WITH THE INDEPENDENCE OF STROKE PATIENTS (Studies In The Inpatient Hospital Caruban) - Ridwan Nor H; . Hariyono; Anita Rahmawati (STIKES Insan Cendekia Medika Jombang, 2014)
The high disability due to stroke every stroke patients resulted in decreased independence in performing activities of daily living. The number of stroke patients who continue to increase until the year 2013 is estimated 500 thousand persons had a stroke. Of this amount, about 2.5% of them died and the rest suffered mild or severe disability, and preliminary studies showed there were 50 stroke patients in the hospital inpatient RSUD Caruban. The purpose of this study to know the Family Relationship Support the Independence of Patients With Stroke (in space Inpatient Hospital RSUD Caruban).Analytical study design with a cross-sectional approach. The population of stroke patients in the hospital inpatient RSUD Caruban, as many as 50 patients, with a total sample of 44 sampling using simple random sampling technique. Independent variables in this study Family Support, Dependent Variable is the independence of Stroke Patients. Instrument in the form of questionnaires. Analysis of data through editing, coding, scoring, tabulating the Spearman Rank's test.The results showed that the relationship with the family support independence of stroke patients Spearman Rank's test statistics obtained significant numbers or probability value (0.002) significantly lower standard of 0.05 or ( <), then H1 is accepted and H0 is rejected, which means There Family Relations Support the Independence of Stroke Patients. It can be concluded that there is a family relationship support the independence of stroke patients in the hospital inpatient RSUD Caruban.Keywords: Family Support, Independence, Stroke.